2005
DOI: 10.1021/bi0510577
|View full text |Cite
|
Sign up to set email alerts
|

Thrombomodulin Tightens the Thrombin Active Site Loops To Promote Protein C Activation

Abstract: Thrombomodulin (TM) forms a 1:1 complex with thrombin. Whereas thrombin alone cleaves fibrinogen to make the fibrin clot, the thrombin-TM complex cleaves protein C to initiate the anticoagulant pathway. Crystallographic investigations of the complex between thrombin and TMEGF456 did not show any changes in the thrombin active site. Therefore, research has focused recently on how TM may provide a docking site for the protein C substrate. Previous work, however, showed that when the thrombin active site was occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
55
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 31 publications
(77 reference statements)
10
55
1
Order By: Relevance
“…One pathway connects the TM5 domain with ABE1, the 60 CT insertion, and the active site. This allosteric network, which exists in both the thrombin:TM56 and thrombin:TM456 systems, was previously identified using H/D exchange (16). Community network models further indicate that TM4 strengthens this allosteric pathway (Fig.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…One pathway connects the TM5 domain with ABE1, the 60 CT insertion, and the active site. This allosteric network, which exists in both the thrombin:TM56 and thrombin:TM456 systems, was previously identified using H/D exchange (16). Community network models further indicate that TM4 strengthens this allosteric pathway (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…Several studies, including fluorescence (15), hydrogen/deuterium (H/D) exchange (16), and isothermal titration calorimetry (17), have identified changes in the thrombin active site region that occur on binding to different constructs of TM in the absence of protein C. These studies suggest that the presence of TM4 may affect the dynamic properties of both the active site and the loops surrounding it, a process referred to as entropic allostery (18)(19)(20). A very recent NMR/molecular dynamics simulation study on thrombin bound to the inhibitor D-Phe-Pro-Arg-chlorormethyl ketone (PPACK) identified significant dynamic motions in the active site loops across time scales ranging from picoseconds to tens of microseconds even with inhibitor bound (21).…”
mentioning
confidence: 99%
“…As a result, information can still be collected on the full loop region. Prior hydrogen deuterium exchange studies demonstrated that the same conformational conclusions could be made with both thrombin forms (17,28). Moreover, the autolysis loops reported on similar changes in solvent accessibility.…”
Section: Methodsmentioning
confidence: 64%
“…Biophysical studies that probe the conformational features of thrombinligand interactions have yielded similar results for both bovine and human thrombins. Ligands that have been examined include PPACK (28), the thrombomodulin EGF domains (14,17,19), fibrinopeptide A (29), PAR1 (30), and fibrinogen ␥Ј (15). There are some sequence differences between bovine and human thrombin within the autolysis loop region.…”
Section: Methodsmentioning
confidence: 99%
“…TM binds to exosite I of thrombin, remote from the zymogen activation domain, yet affects the rate of cleavage of several substrates, the accessibility of the S1 pocket, and the general features of the active-site cleft (12)(13)(14)(15)(16). These effects are not unique to TM, and apply to any exosite-I-binding ligand, including the C-terminal peptide derived from hirudin (known as hirugen) (16).…”
mentioning
confidence: 99%